A Critical Review on the Book A New Look at the Entrepreneurial Beliefs and Corporate Management - Mohammad Javad Naeiji; Seyyed Mostafa Alemnajafi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The content of A New Look at the Entrepreneurial Beliefs and Corporate Management book comprises three sectors and 13 chapters with the centrality of entrepreneurship and corporate management. Also, an attempt has been made to provide a redefinition of entrepreneurship and related beliefs; although this effort has been futile with the lack of use of new and novel resources. The book mostly relies on reports of the previous decade and has been deprived from domestic reports. Although this book has been able to provide comprehensive knowledge of entrepreneurship and business management in firms by imitating resources from previous decades, it hasn’t been able to explain the relationship between business and entrepreneurship and mainly asks the reader for their judgment on the subject. Also by using phrases such as: the statistics indicate that, or some scientists have said that; tries to confirm its content. Therefore, contrary to the opinion of the writers of the book, it’s not a complete source particularly about the use of internal experience in the area under discussion.